Impact of formative assessment based on feedback loop model on high school students’ conceptual understanding and engagement with physics - Ole, Faith Celeste; Gallos, Marilou R. (Journal of Turkish Science Education, 2023)
This study examined the effects of using the Feedback Loop Model (FLM) in Grade 12 Senior High School (SHS) Physics classes. Using a one-group pretest-posttest design, 58 students identified from a simple random sampling method were tested for their conceptual understanding and engagement with in kinematics. The results showed that students’ engagement had been significantly affected when their physics teachers practised formative assessment (FA) using the Feedback Loop Model in their synchronous classes. These implications were supported by both quantitative and qualitative data in the study. With the use of Wilcoxon Signed-rank Test, statistical differences were obtained in the four dimensions of the engagement tool in terms of agentic engagement (Z = 3.37, p < .001), behavioural engagement (Z = 4.82, p < .001), emotional engagement (Z = 4.06, p < .001), and cognitive engagement (Z = 4.40, p < .001). Meanwhile, for students’ conceptual understanding, the difference between their pre-and posttests mean scores in kinematics revealed a significant difference (t (57) = 17.76, p < .001), suggesting that teachers’ classroom practices towards FA using FLM affected students’ level of conceptual understanding in Kinematics. Employing Cohen’s d to measure its practical significance also showed a large effect (d = 2.83). Thus, it is recommended that implementing FA based on FLM could significantly impact the engagement and learning process of high school physics students.